Comprehensive analysis of the interaction microbiome and prostate cancer: an initial exploration from multi-cohort metagenome and GWAS studies - Ye, Gui-Chen; Peng, Hao; Xiang, Jia-Cheng; Miao, Ling-Tao; Liu, Cheng-Zhi; Wang, Shao-Gang; Xia, Qi-Dong (Journal of translational medicine, 2025)
Prostate cancer is one of the most common cancers in the United States with a high mortality rate. In recent years, the traditional opinion about prostate microbiome was challenged. Although there still are some arguments, an escalating number of researchers are shifting their focus toward the microbiome within the prostate tumor environment. We mined the data of the microbiome extracted from the metagenome, and it offers a broader taxonomic coverage and accurate functional profiling. We used Kraken2, a mapping tool, to mine the gut microbiota of prostate cancer patients. A two-sample Mendelian Randomization was conducted to reflect the association between gut microbiome and cancer. In the study, we found the consistency of the special intratumor microbiome of both non-metastatic tumors and metastatic tumors. And we dig the gut microbiome in patients with different treatments. We found that some microbiotas may be associated with prostate cancer progression and a special microbiome in metastatic prostate cancer may exist. The anti-androgen therapy can significantly change both the intratumor and gut microbiome. With the progression and metastasis of prostate cancer, some intratumor microbiome changes. And anti-androgen influences both the intratumor and gut microbiome. Our discovery may help researchers further understand the progression, metastasis, and resistance of prostate cancer from the perspective of microbiome level.